SISTEM PENDUKUNG KEPUTUSAN BERBASIS WEB UNTUK MENENTUKAN SISWA PENERIMA BANTUAN PIP MENGGUNAKAN METODE TOPSIS - fauzi, umar; Indriyanti, Aries Dwi; Vitadiar, Tanhella Zein; Mufarrihah, Iftitaahul (Fakultas Teknologi Informasi, 2025)
Education is an important element in nation building, with the Smart Indonesia Programme (PIP) as one of the government initiatives to improve access and quality of education for students from economically weak families. However, the implementation of PIP often faces obstacles in the selection of beneficiaries, especially in manual processes that are prone to subjectivity and human error. This research aims to develop a web-based decision support system with the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method to improve the objectivity, efficiency, and accuracy of PIP beneficiary selection at MI Al-Adnani, Jombang.The research was conducted through the stages of analysis, data collection, and method implementation. The TOPSIS method was chosen because of its ability to handle uncertainty in decision-making by considering various criteria such as parents‘ income, number of family dependents, parents’ occupation, orphan status, and ownership of KIP and PKH cards.The results showed that the application of the TOPSIS method was successfully integrated into a web application, resulting in a ranking of students who are eligible to receive assistance objectively and transparently. In a comparison test of calculations using the TOPSIS method between the system and Excel, the same recommendation of students receiving aid was obtained, with the highest scores for Amrullah Rafie Purnawan (0.7), Muhammad Afnan Atma Purnama (0.7), and Hayqo Mazaya (0.6). This application is proven to be effective in reducing subjectivity, increasing selection accuracy, and providing transparency to the school so that it can be a quick and efficient solution in the distribution of educational assistance at MI Al-Adnani. Keywords: Indonesia Smart Program, Decision Support System, TOPSIS, Website